2018 IEEE International Symposium on Information Theory (ISIT) 2018
DOI: 10.1109/isit.2018.8437667
|View full text |Cite
|
Sign up to set email alerts
|

Near-Optimal Noisy Group Testing via Separate Decoding of Items

Abstract: The group testing problem consists of determining a small set of defective items from a larger set of items based on a number of tests, and is relevant in applications such as medical testing, communication protocols, pattern matching, and more. In this paper, we revisit an efficient algorithm for noisy group testing in which each item is decoded separately (Malyutov and Mateev, 1980), and develop novel performance guarantees via an information-theoretic framework for general noise models. For the special case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 41 publications
3
28
0
1
Order By: Relevance
“…For the achievability part, we propose an adaptive algorithm whose first stage can be taken as any non-adaptive algorithm that comes with partial recovery guarantees, and whose second stage (and third stage in a refined version) improve this initial estimate. By letting the first stage use the information-theoretic threshold decoder of [8], we attain an achievability bound that is near-tight in many cases of interest, whereas by using separate decoding of items as per [13], [16], we attain a slightly weaker guarantee while still maintaining computational efficiency. In addition, we provide a novel converse bound showing that Ω(k log k) tests are always necessary, and hence, the implied constant in any scaling of the form n = Θ k log p k with k = Θ(p θ ) must grow unbounded as θ → 1.…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the achievability part, we propose an adaptive algorithm whose first stage can be taken as any non-adaptive algorithm that comes with partial recovery guarantees, and whose second stage (and third stage in a refined version) improve this initial estimate. By letting the first stage use the information-theoretic threshold decoder of [8], we attain an achievability bound that is near-tight in many cases of interest, whereas by using separate decoding of items as per [13], [16], we attain a slightly weaker guarantee while still maintaining computational efficiency. In addition, we provide a novel converse bound showing that Ω(k log k) tests are always necessary, and hence, the implied constant in any scaling of the form n = Θ k log p k with k = Θ(p θ ) must grow unbounded as θ → 1.…”
Section: Contributionsmentioning
confidence: 99%
“…• The method of separate decoding of items, also known as separate testing of inputs [13], [16], also considers the items separately, but uses all of the tests. Specifically, a given item's status is selected via a binary hypothesis test.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…• In the non-adaptive setting with symmetric noise, it was shown in [10], [22] that an information-theoretic threshold decoder attains the bound (14) when k = Θ(p θ ) for sufficiently small θ > 0. The analysis of [15,Appendix A] shows that analogous findings also hold for the Z and RZ noise models.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, a given item's status is selected via a binary hypothesis test. This method was studied for k = O(1) in [20], and for k = Θ(p θ ) in [14]. In particular, it was shown that for the symmetric noise model, the number of tests is within a factor log 2 of the optimal information-theoretic threshold as θ → 0.…”
Section: Related Workmentioning
confidence: 99%